Revised distribution and plant communities of Orobanche alsatica and notes on the Orobanchaceae series Alsaticae in Poland - Piwowarczyk, Renata (Biodiversity: Research and Conservation, 2012)
The paper presents the current distribution of Orobanche alsatica in Poland, based on a critical revision of herbarium and literature data and on my field studies conducted in 2006-2011. The recorded localities are mainly in Polish Uplands: the Lublin Upland (Wyżyna Lubelska), Roztocze, and Polesie, less frequently in the Małopolska Upland (Wyżyna Małopolska) and Silesia-Kraków Upland (Wyżyna Śląsko-Krakowska). Distribution maps of O. alsatica and other species of the series Alsaticae (O. bartlingii and O. mayeri) in Poland are included. Their taxonomy, biology, ecology, and habitat preferences are also discussed.